Correlation Study: Student Perceptions of The Use of Learning Technology with Learning Outcomes - Ridwan Sudirman; Andrian Rahman Ayudi; Taufik Hidayat Suharto; Habib Cahyono, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to determine student perceptions on the use of learning technology on learning outcomes at Setia Budhi Rangkasbitung University. This type of research is quantitative with a correlational approach. Perception data collection in the form of a questionnaire was carried out online via Google Form for 97 students who were taking adaptive physical education courses at Setia Budhi University Rangkasbitung. Learning outcome data collection used final semester exam scores, determining the sample using purposive sampling techniques. The data analysis technique uses Pearson Correlation Product Moment analysis. The results of the research show that there is a significant relationship between student perceptions of the use of learning technology and learning outcomes, with r calculated 0.552 > r table (df 96; 5%) 0.199 and a significant value of 0.000 < 0.05. Student perceptions on the use of learning technology have a relationship with learning outcomes of 30.50%. These results show that if students' perceptions of the use of learning technology are better, then learning outcomes will be better.